Governmental learning as a determinant of economic growth - Marina Gruševaja (Leibniz Institute of Agricultural Development in Central and Eastern Europe (IAMO), 2011)
Systemic economic transition is a process of determined radical institutional change, a process of building new institutions required by a market economy. Nowadays, the experience of transition countries with the implementation of new institutions could be reviewed as a method of economic development that despite similar singular steps has different effects on the domestic economic performance. The process of institutional change towards a market economy is determined by political will, thus the government plays an important role in carrying out the economic reforms. Among the variety of outcomes and effects the attention is drawn especially to economic growth that diverges significantly in different post-transition countries. The paper attempts to shed light upon the problem on the basis of institutional economics, of economics of innovation and partially of political economy of growth using an evolutionary, process-oriented perspective. In this context the issue central to the promotion of economic growth is the successful implementation of new institutions through governmental activities. The paper shows that under the conditions of bounded rationality and radical uncertainty economic growth is determined, inter alia, by the capacity for governmental learning. Keywords: institutional change, governmental learning, economic growth
Keywords: B52; D80; O43; 330